A Reliability Analysis of Steam Condenser Instrumentation Using Failure Mode and Effect Analysis (FMEA) - M.Padol Padilla; Jufrizel; Putut Son Maria; Ahmad Faizal (APIC, 2024)
Abstract—PT PLN Nusantara Power UP Tenayan is a steam power plant (PLTU) with a capacity of 2 x 110 MW which is a buffer for the electricity system in the Central Sumatra section. In the production process of PT PLN Nusantara Power UP Tenayan it does not always go well,. So that it will have an impact on the production stages of the power plant. One of the production machines that often fails and disrupts the production stage is the steam condenser. This research uses the Failure Mode And Effect Analysis Method which aims to identify the type of failure, cause of failure, effect of failure, and determine the RPN value. The research phase begins with data collection from literature studies, interviews, field observations, data analysis, FMEA analysis, results and discussion, conclusions. Based on the results of the RPN calculation, each component of the steam condenser instrumentation does not exceed the RPN standard limit of less than 200, although the temperature indicator has the highest RPN value but is still categorized as reliable and not recommended for immediate maintenance action. The results of identifying the type of failure are that there are inaccurate indications, there are switches with sticky conditions, there are displays that are unclear or blurry, and there is a mismatch between the data displayed in the DCS and the data displayed in the local area. For recommended actions on the steam condenser instrumentation components, among others, carry out more incentive maintenance every 3 months, make improvements to the specifications of the switch according to the amount of pressure to be measured, move the sensor to a safer area and protected from water exposure, carry out a zero calibration process on the steam condenser instrumentation components every six months.